Assistência às vítimas de crimes em Alagoas: limites e possibilidades - Pereira, Juliana Pedrosa (2008)
Today the violence is one of the most difficult social problem of Brazil and Alagoas, and inevitably involves issues related to the political process and socio-economics that we face over time. To fight this great evil has been the rule valid for new policies that aim to reverse this lack forward to increased crime. Among these policies emerge concern to assist the victims of crimes, their families and dependents. This research has as main focus whether and to what extent the assistance to victims of crime interferes with the reduction in rates of violence in society today. This study shows the social origins of human rights and the movement in defense of victims of crime, considering the particularities of public policies in Brazil and especially the peculiarities of assistance to victims of crime in Alagoas. The study presents a critical about assistance to victims of crime, showing the consequences resulting from the current moment of capitalism in human rights policies, reasons it is impossible to abandon the relationship between crime and the peculiarities of the capitalist mode of production. Finally, based the Marxist theoretical framework, it was shown that assistance to victims of crime does not meet the purpose for which it proposes, to combat crime and decrease rates of violence because it is a proposal for public policy within the system capitalist who does not bring the possibility of overcoming the problem itself.